Severe neuropsychiatric systemic lupus erythematosus successfully treated with rituximab: an alternative to standard of care - Chessa E (Dove Medical Press, 2017)
Elisabetta Chessa, Matteo Piga, Alberto Floris, Alessandro Mathieu, Alberto Cauli Rheumatology Unit, University Clinic AOU of Cagliari, Cagliari, Italy Abstract: Demyelinating syndrome secondary to systemic lupus erythematosus (DS-SLE) is a rare encephalomyelitis burden with a high risk of disability and death. We report on a 49-year-old Caucasian woman with systemic lupus erythematosus (SLE) complicated by severe cognitive dysfunction, brainstem disease, cranial nerve palsies, weakness and numbness in limbs and multiple discrete magnetic resonance imaging (MRI) areas of damage within the white matter of semioval centers, temporal lobe, external capsule, claustrum, subinsular regions and midbrain. She also had multiple mononeuritis diagnosed through sensory and motor nerve conduction study. She was diagnosed with severe DS-SLE prominently involving the brain and was treated with 500 mg methylprednisolone (PRE) pulses for 3 consecutive days, followed by one single pulse of 500 mg cyclophosphamide, and 1 g rituximab, which was then repeated 14 days later. PRE 25 mg/day, rapidly tapered to 7.5 mg/day in 6 months, and mycophenolate mofetil 1 g/day were prescribed as maintenance therapy. She had progressive and sustained improvement in neurological symptoms with almost complete resolution of brain MRI lesions after 1 year. B-cell depleting therapy could be considered as a possible alternative to standard of care in the management of severe inflammatory neuropsychiatric SLE but it should be associated with a conventional immunosuppressant as maintenance treatment to reduce the risk of flare and reduce corticosteroids dose. Keywords: systemic lupus erythematosus, neuropsychiatric lupus, rituximab, demyelinating syndrome, brain MRI